KEPUASAN KERJA DAN DISIPLIN KERJA PENGARUHNYA TERHADAP MOTIVASI KERJA KARYAWAN PDAM TIRTA BHAGASASI BEKASI - Evi Mafriningsianti (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2020)
This research objective to determine the satisfaction, discipline, and motivation of employees of PDAM Tirta Bhagasasi Bekasi, and also to determine satisfaction and discipline of influence on work motivation the employee of PDAM Tirta Bhagasasi Bekasi. There are 90 employees of PDAM Tirta Bhagasasi Bekasi as a sample in this study. The sampling technique uses simple random sampling techniques. Observation and questionnaire methods are used in collecting the data. The data analysis technique uses multiple regression analysis with the SPSS program. The results of the descriptive analysis show the good realization of job satisfaction (average score 3.63) and employee work discipline (average score 3.61) so that it has a positive impact on employee work motivation (average score 3.57). These results are supported by Bekasi Tirta Bhagasasi PDAM data in 2018 which obtained a level of realization of workforce satisfaction of 61.38 percent (sufficient category), the value of realization of employee work discipline at 5.80 percent (sufficient category), and the level of realization of labor motivation of 60.71 percent (sufficient category). t value calculated job satisfaction (b1) = 9,133 with a significance of 0,000 (less than= 0.05) then Ho is rejected and Ha is accepted. This means that job satisfaction has a significant effect on the work motivation of PDAM Tirta Bhagasasi Bekasi employees. T value is calculated work discipline (b2) = 5.535 with a significance of 0,000 (less than= 0.05) then Ho is rejected and Ha is accepted. This means that work discipline has a significant effect on the work motivation of PDAM Tirta Bhagasasi Bekasi employees.